Особливості обліку торгівельних знижок на підприємствах торгівлі та відображення їх у фінансовій звітності - Букало, Надія Артемівна; Bukalo, Nadiia A.; Новицька, Ю. В.; Novytska, Yu. V. (Мукачівський державний університет, 2016)
У статті досліджено економічне поняття «знижки», наведено його визначення вітчизняними та зарубіжними вченими. Систематизовано різні види торговельних знижок та визначено методологічні особливості їх бухгалтерського обліку та відображення у звітності на торговельному підприємстві. The topical problem of the reflection of the given trade discounts is considered in the article. The economic concept of a ‘discount’ is investigated; the interpretations of definitions of domestic and foreign scientists are presented and their identities are described. Different kinds of discounts are systemized, among them – discounts for quantity of purchased goods, holiday discounts, seasonal discounts, and discounts for the purchase of goods over a specified price, special discounts, confidential discounts, bonus discounts and cash discounts. The features of reflecting the accounting of giving discounts before the good realization and after it are considered. The kinds of special discounts of a particular enterprise are discussed.
The features of trade discounts’ accounting of enterprises and
Keywords: Підприємство; знижка; ціна; бонус; акція; discount; company; price; bonus shares